2015
DOI: 10.1128/aac.04821-14
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Extended-Spectrum β-Lactamase Production on Treatment Outcomes of Acute Pyelonephritis Caused by Escherichia coli in Patients without Health Care-Associated Risk Factors

Abstract: T he recent increase in extended-spectrum ␤-lactamase (ESBL) producers among community Escherichia coli isolates has been of great concern worldwide. In previous studies, recent contact with the health care system was identified as a major risk factor for community onset ESBL-producing E. coli (ESBL-EC) infections (1-3). However, ESBL-EC is causing increasing numbers of community onset infections, especially urinary tract infections (UTIs), among patients without health care-associated (HCA) risk factors, i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 31 publications
4
19
0
2
Order By: Relevance
“…In our series, 97% of patients were cured, just like Qureshi et al13 and Chapman et al16 reported in their series. In other series, the readmission of patients reported was around 6.3% over a period of 2 years; however, in our series only 3% of the patients required readmission.…”
Section: Discussionsupporting
confidence: 84%
“…In our series, 97% of patients were cured, just like Qureshi et al13 and Chapman et al16 reported in their series. In other series, the readmission of patients reported was around 6.3% over a period of 2 years; however, in our series only 3% of the patients required readmission.…”
Section: Discussionsupporting
confidence: 84%
“…Age over 55 years (OR: 2.0, 95% CI: 1.0–3.5) 30 and male sex (OR: 1.6, 95% CI: 1.2–2.1 in the higher quality study by Søgaard et al) 38 also have been reported as risk factors for UTI due to ESBL-producing E. coli .…”
Section: Resultsmentioning
confidence: 99%
“…Studies #7 and #10 had fewer than 25% of UTIs among the total infections in the group. CBP was not significantly superior to non-CBP agents in the studies that included 40% or more of UTIs among the total infections (studies #4–6 [ 4 , 12 , 13 ], #8 [ 14 ], #9 [ 15 ], #11 [ 16 ]).…”
Section: Main Textmentioning
confidence: 99%